2013
DOI: 10.2147/copd.s53590
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors associated with the humoral immune response to influenza vaccination in chronic obstructive pulmonary disease

Abstract: Background and objectiveIndividuals with chronic obstructive pulmonary disease (COPD) are at a high risk of developing significant complications from infection with the influenza virus. It is therefore vital to ensure that prophylaxis with the influenza vaccine is effective in COPD. The aim of this study was to assess the immunogenicity of the 2010 trivalent influenza vaccine in persons with COPD compared to healthy subjects without lung disease, and to examine clinical factors associated with the serological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 26 publications
0
65
0
2
Order By: Relevance
“…These have major issues with the constant need for developing new vaccines. COPD patients respond poorly to vaccination, as IAVs have become drug resistant and all therapeutics have questions surrounding availability and efficacy in future pandmics (22,23). There is therefore an urgent need to develop novel therapeutics for influenza, especially for those most susceptible to infection.…”
Section: Introductionmentioning
confidence: 99%
“…These have major issues with the constant need for developing new vaccines. COPD patients respond poorly to vaccination, as IAVs have become drug resistant and all therapeutics have questions surrounding availability and efficacy in future pandmics (22,23). There is therefore an urgent need to develop novel therapeutics for influenza, especially for those most susceptible to infection.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly little research documents the immune response to TIV among patients with COPD. One observational study conducted in Australia found that patients with COPD produce a lower-fold increase in antibody concentrations in response to TIV, concluding that individuals with COPD mount a reduced humoral immune response to the influenza vaccine [Burel et al 2012;Nath et al 2014]. This study found that 90% of healthy subjects showed seroconversion in response to TIV compared with only 43% of patients with COPD.…”
Section: Measuring Vaccine Success: Immunogenicity and Beyondmentioning
confidence: 94%
“…One randomized, controlled study conducted in the Netherlands demonstrated no statistically significant difference in the efficacy of the influenza vaccine between smokers and nonsmokers in an older population [Cruijff et al 1999]. Additionally, another observational study concluded that there was no association observed between influenza vaccine response and whether the study participant was a current smoker [Nath et al 2014]. More research is needed before concluding there is an effect of smoking on the vaccine immunogenicity of TIV, but the evidence would suggest that TIV plays a key role in smokers and exsmokers with COPD.…”
Section: Smoking and Vaccine Responses In Copdmentioning
confidence: 99%
“…Finally, host factors in addition to age that may impact vaccine efficacy include nutrient status, microbiome of the individual, metabolic or disease condition, psychosocial factors, health practices, and previous infection history. [293][294][295][296][297][298] The "ideal" vaccine will elicit protective immunity regardless of the many genetic, physiological, or psychological conditions that may be present in the host.…”
Section: Host Factorsmentioning
confidence: 99%